Taking to scale adaptable climate smart technologies - Ellis-Jones, J.; Phiri, A.; Chibwe, T.; Gondwe, T.N.P.; Nhamo, N. (Elsevier, 2017)
The strength of an innovation systems approach for Integrated Agriculture Research for Development (IAR4D) is based on a wide involvement of stakeholders, capacity building, planned progression of involvement of different actors, and the voluntary nature of participation. In this chapter, this concept is taken further showing that successful pilot initiatives can be taken to scale using and building on the same principles embedded in IAR4D. This requires an understanding of research and development scaling pathways and the use of participatory research and extension approaches in preference to the traditional and linear approaches used in the past. Looking to the future involvement of a wide range of actors from both the agriculture sector and beyond is essential for building a sustainable innovation system. At the same time increasing use of Internet and mobile networks provide opportunity for improving access to knowledge that can speed the scaling process.